Bird Communities In Seblat Nature Recreation Park (SNRP) North Bengkulu, Bengkulu - Eki Susanto; Yeni Aryati Mulyani; Bambang Suryobroto (Biosaintifika: Journal of Biology & Biology Education, 2016)
Bird communities are the composition of several bird species that live together in the same place, time and interact with other birds. The diversity of birds in an area can be used as an indicator of stabilizing an area. Changes of vegetation structures due to logging practices can affect the availability of resources for bird communities. The objective of the research was to examine diversity, richness, bird species abundance and bird community similarity at HS1 (logged forest 1974), HS2 (logged forest 1989/1990) and HS3 (fully logged forest 1989/1990) in Seblat Nature Recreation Park (SNRP). The research was conducted in July – September 2013. Data collection was conducted by point count method (total 36 points) and mist net method (total 4752 nets hours). The Research showed 85 bird’s species from 33 families were recorded. HS2 was highest value of diversity and richness (H ‘= 3.63, DMG = 10.07). The highest relative abundance species in HS1 was Emerald Dove (Chalcophaps indica), while HS2 and HS3 were Slender-billed Crow (Corvus enca). The bird community similarity was highest in HS2 and HS3 (ISj = 0.58).How to CiteSusanto, E., Mulyani, Y. A., Suryobroto, B. (2016). Bird Communities In Seblat Nature Recreation Park (SNRP) North Bengkulu, Bengkulu. Biosaintifika: Journal of Biology Biology Education, 8(1), 25-32.